PERAN TEMAN SEBAYA DALAM MENGATASI KRISIS PERCAYA DIRI PADA SISWA SMPIT BINA BANGSA - Mutias, Alya Sabrina; Amroh, Amroh; Hisyam, Nabil Alif; Rahmi, Della Danita; Sulasti, Lulu Andriani; Ayuningtiyas, Vidya (STAI Darul Qalam Tangerang, 2026)
This study aims to analyze the role of peers in overcoming self-confidence crises among 7th and 8th grade junior high school (SMP) students. Self-confidence crises are a common problem during early adolescence and can lead to low levels of academic engagement and social interaction among students. This study employs a qualitative, descriptive approach. Data collection techniques included open-ended questionnaires, observation, and in-depth interviews. The results indicate that students tend to experience a self-confidence crisis characterized by fear of making mistakes, shyness, and a reluctance to speak up in class. However, the presence of peers has a positive influence, as students become more confident, active, and self-assured when supported by their peers. Peers serve as sources of emotional support, motivation, and social models that help students boost their self-confidence. The conclusion of this study indicates that self-confidence crises among students are situational in nature and can be overcome through a positive peer environment.